A Questionnaire Study to Assess Level of Knowledge, Awareness and Management of Mucormycosis Among Prosthodontists working in dental hospitals/teaching institutions in Pune District. (Journal of Pharmaceutical Negative Results, 2023)
Aim:  The objectives of study were to assess the knowledge, awareness and management of mucormycosis among Prosthodontists working in dental hospitals/ teaching institutions in Pune, India. and to find out the association between the level of knowledge, awareness and management of mucormycosis and selected demographic variables. Methods: Descriptive survey was done through online questionnaire using Google forms software distributed to all 98 participants of six dental hospitals/ teaching institutions in Pune through their Mail-Id. The data analysis was done using the Statistical Package for Social Sciences (SPSS) statistical software, version 19.0. Results: All the 98 participants responded, though only less than half of the population (48% from age group 20-30 years) was aware about that infection will not transmit from dentist to dentist. Statistically significant differences in knowledge about mucormycosis among the various highly experienced and designated doctors and residents were found as level of knowledge increased with the seniority. The study also shows that more than half about 63% of participants have rehabilitated the case of mucormycosis and among them 40% people observed some kind of difficulties for impression making or fitting of prosthesis.  Conclusion: Though our study showed average number of participants have adequate knowledge about mucormycosis, only more than half of the population particularly from age group 20-30 years was having less knowledge and awareness. Hence, our study concludes that there is a need for an increased awareness among young prosthodontist regarding the same.